Haptic Search in Divided Areas: Optimizing the Number of Divisions1. (1st March 2017) - Kaga, Hirotsugu; Kawaguchi, Chihiro; Mishina, Midori; Kita, Shinichi; Watanabe, Tetsuya
Abstract: The present study investigates the efficiency of haptic search facilitated by the division of the searchable area. Previous studies have shown that scales provided around tactile maps for blind persons can shorten the search time for tactile symbols on the maps, but the optimum number of divisions has not been found. We conducted an experiment in which maps with different numbers of divisions were presented to blindfolded participants. The search times for tactile targets on the maps were measured and a movie that recorded searching behavior was analyzed. Our results indicate that scales with 3 × 4 divisions minimize search time, and the movie analysis reveals that this optimization is determined by the time of both scale‐counting and target‐searching. This finding elucidates the manner of human haptic search and should be utilized for the optimization of automated tactile map creation.